Healthy Living for Elders: Exercise and Diabetes - Sergio Romero (EDIS)
Exercise is one of the best things you can do for your health. Exercise can help you control your blood sugar levels, reduce body fat, and decrease your risk of heart disease. This leaflet contains some tips to help you create a fun and healthy exercise program. Start today!